Case Report: Isolated Idiopathic Saccular Dysfunction - Waissbluth, Sofia; Oyarzún, Javier (Frontiers in Neurology, 2021)
Advances in vestibular testing have now allowed us to test each semicircular canal as well as the utricle and saccule, independently. This has led to the discovery of new patterns of vestibular dysfunction that were once impossible to evaluate. This report describes the case of a 20-year-old woman with a two-month history of recurrent dizziness. She had a complete audiovestibular assessment. The only abnormality observed was the absence of a cervical vestibular-evoked myogenic potential response for the right side, hence, an isolated saccular dysfunction. In conclusion, isolated otolithic dysfunction is probably an overlooked and neglected clinical presentation. Its true incidence is unknown and further research is needed to understand this clinical entity.